Effect of Feeding Cumin (Cuminum cyminum) on the Performance and Some Blood Traits of Broiler Chicks - Al-Kassi, Galib A.M. (Pakistan Journal of Nutrition, 2009)
This study was conducted to identify the effect of using cumin (Cuminum cyminum) on the performance and some blood traits of broilers. Two hundred one day-old unsexed broiler chicks (Arbor-Acres) were divided into four groups of 50 birds each and assigned to four feeding treatments. Group 1 is considered as a control group where there was no addition of Cuminum cyminum. Group 2, 3 and 4 involved the addition of 0.5, 1 and 1.5% of Cuminum cyminum respectively. The results showed that group 2 and group 3 performed significantly higher (p<0.05) in the average live weight, weekly weight gain, feed consumption, mortality rate and feed conversion ratio. Results showed that chicks in treatment 3 developed a significant decrease in the level of cholesterol in blood serum compared to other treatments.